The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1957
DOI: 10.3133/pp282b
|View full text |Cite
|
Sign up to set email alerts
|

River channel patterns: Braided, meandering, and straight

Abstract: A. Analyses of sand sizes used in flume experiments and fed into flume-river. _ _ _ _. _ _ _ _ _ _ _ B. Data o n size characteristics of sand on channel bed and on bars in flume-river.__ _ _ _ _ _~-~- .- .-C. Summary of data on flume experiments a t California Institute of Technology .__._-~ ~. .- .-D. Comparison of hydraulic characteristics of uiidivided and divided reaches of braided streams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
795
2
30

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,108 publications
(896 citation statements)
references
References 0 publications
31
795
2
30
Order By: Relevance
“…In order to test for possible fluvial channels, morphometric measurements were made on the sinuosity and width of four of the largest channels (identified in Figures 1 and 7) and the length versus width of the streamlined islands. An investigation of meandering terrestrial rivers by Leopold and Wolman (1957) showed that bank full width (W) is related to wavelength (X) by the following relationship h = KW'. '…”
Section: Channel Originmentioning
confidence: 99%
“…In order to test for possible fluvial channels, morphometric measurements were made on the sinuosity and width of four of the largest channels (identified in Figures 1 and 7) and the length versus width of the streamlined islands. An investigation of meandering terrestrial rivers by Leopold and Wolman (1957) showed that bank full width (W) is related to wavelength (X) by the following relationship h = KW'. '…”
Section: Channel Originmentioning
confidence: 99%
“…Ikeda et a1 (1981) extended their analysis to perturbatiC'.....s of channels which were initially sinuous. None of the theories adequately reproduces the sort of behaviour observed by Leopold and Wolman (1957) and others.…”
Section: Discharge (Cusecs)mentioning
confidence: 94%
“…Leopold and Wolman (1957) plotted bankfull discharge against channel slope for a number of natural channels. This indicated that in those rivers the braided channels were separated from the meandering channels by a line given by the equation:…”
Section: Plan Form Of Riversmentioning
confidence: 99%
See 2 more Smart Citations